Penerapan komunikasi dan public relation pada karyawan baru kafe - Hestiyanti, Siti Fatimah (Maliki Interdisciplinary Journal, 2024)
In today's global business, public relations is an element that supports and helps an enterprise or business. Public Relations (PR) itself is also an important aspect in any business, one of which includes cafes. Applying effective communication and public relations to new employees is the key to building a team that is competent, committed, responsible and helpful to each other. Likewise, RS Kafe has also implemented good communication and public relations within it. This aims to enable new employees to understand the work culture, values and goals of the cafe. Apart from that, effective communication and public relations also help cafes respond to challenges situations.